2017
DOI: 10.1186/s13104-017-2578-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial pathogens associated with acute childhood diarrhoea in Kumasi, Ghana

Abstract: BackgroundDiarrhoeal diseases are among the most frequent causes of morbidity and mortality in children worldwide, especially in sub-Saharan Africa. This case–control study was conducted to investigate the bacterial, viral and parasitic pathogens associated with acute diarrhoea among children attending three health facilities in Kumasi, Ghana.MethodsStool specimens were collected from 240 children under 5 years of age visiting hospitals in Kumasi, Ghana due to acute diarrhoea and from 107 healthy controls of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
2
10
1
Order By: Relevance
“…Probably this observation where previously known major sero-groups that caused infection are been overtaken and the less common sero-groups as observed from our study takes the lead. Our finding closely matches to a greater extent the work reported recently in Ghana [41] that Shigella species were generally more common isolates in children below 2 years. Dysentery outbreaks are common especially in developing countries where hygiene and sanitation are questionable.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Probably this observation where previously known major sero-groups that caused infection are been overtaken and the less common sero-groups as observed from our study takes the lead. Our finding closely matches to a greater extent the work reported recently in Ghana [41] that Shigella species were generally more common isolates in children below 2 years. Dysentery outbreaks are common especially in developing countries where hygiene and sanitation are questionable.…”
Section: Discussionsupporting
confidence: 92%
“…Isolation of Salmonella in children above one year and older children above 2 years in our study suggests that the bacteria is less likely to cause infantile diarrhea harmonizing fairly with finding of a study that observed Salmonella infection was more likely to occur as the child's age progressed [38]. More than half of the Salmonella infections were noted to fall within those aged 13-24 months which conforms with a study done in Lusaka Zambia [40] but sharply contradicts finding of a study in Kumasi Ghana that observed those aged 13-24 months were the least infected (1.5%) while those aged 25-60 months were the most infected [41]. Other than probable food/water-borne Salmonella transmission that may occur during complementary feeding, another possible reason of the data observed that more salmonella infections occurred above one year could be that children of older age interact with domesticated animals such as chicken and other fowl within the households as most participants were drawn from rural and semi-urban areas.…”
Section: Discussionmentioning
confidence: 56%
“…Diagnosis of bacterial diseases by conventional culture method usually takes days or weeks after sampling and is not always successful. The overall detection of Shigella in 31.2% of diarrheal cases by ipaH-based PCR in this study is higher than what was reported in Ghana previously [9][10]. PCR has the ability to rapidly identify specific pathogens that are difficult to culture in vitro or require a long cultivation period.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous burden of disease studies in Ghana using traditional culture method documented low prevalence of Shigella in stool samples [9][10]. Diagnosis of bacterial diseases by conventional culture method usually takes days or weeks after sampling and is not always successful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation